The Effect of the Combination of Baby Massage With Boreh Rice Kencur Bima Against Baby Sleep Quality - Eva Sofiana Putri; Linda Meliati; Sudarmi Sudarmi; Intan Gumilang Pratiwi (Jurnal Kesehatan Prima, 2022)
Achieving the need for sleep is an effort that affects the baby's growth. Many millions of children suffer from growth and development problems. In Indonesia, babies who have cases of poor sleep quality wake up a lot at night. Rice kencur boreh is made from rice, and kencur has the benefit of providing warmth and comfort when applied to the body. The people of Bima used to use boreh rice kencur to maintain the health of their babies and make babies sleep soundly. This study aims to determine the effect of the combination of baby massage with rice kencur boreh on improving the quality of baby sleep. This research is a quasi-experimental design with a pre-post test with the control group. The study population in this study were infants aged 3-6 months. The sample consisted of 31 people with a treatment group of 16 people and a comparison group of 15 people-data analysis using Mann Whitney. The results showed an increase in the quality of infant sleep after infant massage with VCO and Boreh Beras Kencur, namely an increase of 3.38 ± 0.44 points. There was also an increase in the control group with average sleep quality of 2.93 ± 0.83 points. There was an effect of the combination of boreh rice kencur Bima on infant sleep quality.